Peat soil behaviour stabilised with by-product of manufacture of edible oils - Habib Musa Mohamad; Anis Anisha Suhaimi; Nur Aqilah Saida; Nelly Majain (GEOMATE International Society, 2025)
Peat settlement is a significant challenge in construction due to its high compressibility, moisture content, poor shear strength, and prolonged settlement behavior under load. Tropical peat soils, in particular, exhibit the highest settlement rates over extended periods, leading to instability in structures built on such soils. These challenges are evident in numerous construction and coastal high-rise projects where peat soil often serves as a foundation material. Despite the critical need, limited research has been conducted on stabilizing peat soils using eco-Processed Pozzolan (EPP). This study investigates peat soil stabilization using EPP through consolidated undrained triaxial tests. The objectives include evaluating the index properties of peat soil, assessing its shear strength under various effective stresses, and analyzing the mechanical properties of EPP-stabilized peat before and after treatment. The results indicate that untreated peat soil recorded shear strength increases of 51.94% at 25 kPa and 186.77% at 50 kPa of effective stress. For EPP-treated peat soil, shear strength improvements were more pronounced. At 25 kPa, T5-25, T10-25, and T15-25 recorded shear strengths of 198.14 kPa, 33.46 kPa, and 21.07 kPa, respectively. At 50 kPa, T5-50, T10-50, and T15-50 exhibited significant increases, with values of 576.77 kPa, 95.72 kPa, and 210.54 kPa, corresponding to percentage increases of 191.09%, 186.07%, and 899.24%, respectively. These findings underscore the potential of EPP in enhancing peat soil properties, offering a sustainable solution for mitigating settlement-related issues.